CERKAS System Development: Smart Web-Based Sharia Accounting as a Learning Media - Purnama Putra; Putra Wisnu Agung Sucipto; Alto Wirahadi Kusuma; Innaroh Hamidah (JRAK: Journal of Accounting Research and Computerized Accounting, 2022)
The COVID-19 pandemic is a virus that has shaken the world, including Indonesia. The existence of the COVID-19 pandemic has dealt a very hard blow in every sector of Indonesian people's lives. One of the sectors affected by the COVID-19 pandemic is in the education sector. Distance learning has become a new problem in the world of education, but on the other hand, research and creativity have emerged in adjusting to the manufacture of learning media aimed at increasing students' motivation and competence. Research in the form of developing this system using the ADDIE (Analysis, Design, Development, Implementation,Evaluation ) method creates a web-based application called CERKAS: Smart Syariah Accounting which seeks to provide solutions to distance learning problems, more specifically for Islamic banking majors at the Vocational High School level. (SMK). The CERKAS web-based application was tested by asking for validation from the experts and the research object, namely 70 students of Islamic banking majoring in Islamic banking. Experts were given questionnaires related to material, application (easiness and appearance), language while respondents from students were given questionnaires in the form of: convenience, appearance, completeness of learning facilities, learning process, learning impact. The results obtained are based on the views of experts and research respondents that the CERKAS application in the category is very feasible to be applied and implemented as a learning media.